Production of jet fuel precursor monoterpenoids from engineered Escherichia coli. Issue 8 (18th May 2017) - Mendez‐Perez, Daniel; Alonso‐Gutierrez, Jorge; Hu, Qijun; Molinas, Margaux; Baidoo, Edward E.K.; Wang, George; Chan, Leanne J.G.; Adams, Paul D.; Petzold, Christopher J.; Keasling, Jay D.; Lee, Taek S.
ABSTRACT: Monoterpenes (C10 isoprenoids) are the main components of essential oils and are possible precursors for many commodity chemicals and high energy density fuels. Monoterpenes are synthesized from geranyl diphosphate (GPP), which is also the precursor for the biosynthesis of farnesyl diphosphate (FPP). FPP biosynthesis diverts the carbon flux from monoterpene production to C15 products and quinone biosynthesis. In this study, we tested a chromosomal mutation of Escherichia coli 's native FPP synthase (IspA) to improve GPP availability for the production of monoterpenes using a heterologous mevalonate pathway. Monoterpene production at high levels required not only optimization of GPP production but also a basal level of FPP to maintain growth. The optimized strains produced two jet fuel precursor monoterpenoids 1, 8‐cineole and linalool at the titer of 653 mg/L and 505 mg/L, respectively, in batch cultures with 1% glucose. The engineered strains developed in this work provide useful resources for the production of high‐value monoterpenes. Biotechnol. Bioeng. 2017;114: 1703–1712. © 2017 Wiley Periodicals, Inc. Abstract : Monoterpenoids (C10 isoprenoids) can be used as precursors for high energy density fuels such as jet fuels. A heterologous mevalonate pathway and a chromosomal mutation of Escherichia coli's native FPP synthase (IspA) have been engineering to improve the availability of GPP, the substrate for monoterpenoid biosynthesis. We discovered that the monoterpenoid production at high levels requires not only the high level of GPP production but also a basal level of FPP production to maintain the growth of the producing host.